Hungarian Monitoring, 23 January 1989 . [Magyar rádiófigyelő], 1989. január 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Scowcroft does not believe that the Cold War is over - Rude Pravo publishes opinion of Czechoslovak youth who wanted to visit Jan Palach's grave - Talks between Czechoslovakia and the Vatican - Carlsson in the GDR - American journalist deported from Romania - Karabakh under new control - Dumas's Israeli talks - Comecon executive committee discusses transforming methods of cooperation Domestic Affairs: - Academic conference on the history of the Hungarian coat of arms and flag; proposal to reinstate Kossuth coat of arms - Transport and construction committee discusses need for housing renovations in city centers; slow progress in evaluation of state-owned apartments - People's colleges closed in 1947-48 to be reformed - Public Sphere Club becomes national association - Gyula Horn in Geneva - Gabčíkovo-Nagymaros dam: no money to build Czechoslovak water purifier - Transylvanian Hungarians - Debate on location of 1995 World Exposition Economy: - Within the Economic Chamber, the interest organisation of business leaders has been formed Külpolitika: - Scowcroft nem hiszi, hogy véget ért a hidegháború - A Rude Pravo CS fiatalok véleményét közli, akik fel akarták keresni Jan Palach sírját - Tárgyalások Csehszlovákia és a Vatikán között - Carlsson az NDK-ban - Kiutasítottak Romániából egy amerikai újságírót, - Karabah az új irányítás alatt - Dumas izraeli tárgyalásai - A KGST-vb az együttműködési módszerek átalakításáról tárgyal Belpolitika: - Tudományos ülés a magyar címer és zászló történetéről. Javaslat a Kossuth-címer visszaállítására - Közlekedési és építési bizottsága a városközpontokban szükséges lakásfelújításokról tárgyalt; lassan halad az állami lakások értékesítése is - Újjáalakulnak az 1947-48-ban beszüntetett népfőiskolák - Országos egyesületté szerveződött a Nyilvánosság Klub - Horn Gyula Genfben - Bős-nagymaros ügy: nincs pénz a Csehszlovákia szennyvíztisztító megépítésére - Az erdélyi magyarok ügye - Vita az 1995-ös világkiállítás színhelyéről Gazdaság: - A Gazdasági Kamara keretében létrejött a gazdasági vezetők érdekképviseleti szervezete